Kepuasan Kerja Guru-Guru Siswazah Sekolah Menengah di Daerah Kubang Pasu, Kedah - Md Nasir, Haji Moin (1996)
The purpose of this research is to investigate the work satisfaction among graduate secondary school teachers in Kubang Pasu district, Kedah and the factors influencing it. In this research, the independent variables are Hierarchy of Needs Theory that are self-actualization, esteem social, relations, safety and physiology. Work satisfaction is the dependent variable. Two hundred and thirty graduate teachers from ten secondary schools from this district were chosen. The instruments used were structured questionnaires. The schools were randomly selected. Data collected were analysed using the Statistical Packages For The Social Science (SSPS) version 6.0 Windows. Beside descriptive statistics,inferential statistics were tested by using Pearson Correlation t-tests and One way Varian Analysis.The significant level used to test the hypotesises was below 0.05 (p < 0.05 ). The results shows i) No significant difference among sex, we, marital status, racial, academic qualification, work period, salary and school grade with work satisfaction among graduate secondary school teachers in Kubang Pasu district, Kedah. ii) Safety was the most important human needs factor which had the significant relation with work satisfaction of graduate teachers. It was followed by self-actualization, esteem, social relations and physiology.